Factors influencing effective integration of educational technology in the colleges of teacher education in Ethiopia: A constructivist grounded theory - Woldemariam, Misganaw; Ergado, Amanuel; Jimma, Worku (Australasian Journal of Educational Technology, 2025)
Integrating educational technology (EdTech) in colleges of teacher education (CTEs) in developing countries presents complex challenges influenced by various factors. In Ethiopia, where research on this subject is limited, these institutions, which play a critical role in preparing future educators, remain unexplored. This study explores the contextual factors affecting teacher educators' EdTech integration and formulates a theoretical framework. Employing constructivist grounded theory, the study was conducted in four Ethiopian CTEs. Data were gathered through semi-structured interviews, structured observations and document analysis, with 23 participants selected via purposive and theoretical sampling. The study identified teacher educator-related and external factors as crucial determinants of EdTech integration. Institutional readiness was a key external factor, while teacher educators’ digital competence and readiness to integrate technology were central internal factors. A theoretical framework was co-constructed to illustrate the interplay of these factors and their influence on EdTech integration. It aligns with activity theory and extends the technology acceptance model and the unified theory of acceptance and use of technology. The credibility of the findings was validated through a member-checking survey. The study recommends quantitative research to pinpoint the most predictive factors and to assess the framework's applicability in developing countries. Implications for practice or policy: In developing countries, CTEs should strategically plan and execute professional development programs, align training with UNESCO’s ICT competency framework, establish technology infrastructure, facilitate technical support and motivate teacher educators to engage in EdTech initiatives. Ministries of education and regional education bureaus should develop and enforce institutional EdTech policy and facilitate EdTech integration into the curriculum. Teacher educators should participate in workshops, seminars, and online courses to stay updated with EdTech tools and digital pedagogy.